The Influence of Internal and External Factors of Banks on the Profitability of Regional Development Banks in Indonesia - Utami Tyas; Lutfi Lutfi (Dinasti Publisher, 2025)
Banking is a crucial component of the financial sector, serving as the backbone of a country's economy. It functions as an intermediary institution that gathers funds from surplus parties and distributes them to those in need. As a business entity, banks inherently aim to generate profits while fulfilling their roles as financial intermediaries and development agents (Garr & Awadzie, 2021). This study aims to analyze the impact of internal factors—such as credit distribution, capital participation, liquidity, fee-based income, and bank size—as well as external factors like GDP on the profitability (ROA) of conventional Regional Development Banks (BPD) in Indonesia from 2013 to 2023. Utilizing panel data analysis with 23 samples, the findings reveal that credit distribution, fee-based income, and GDP do not significantly affect profitability. In contrast, capital participation and liquidity have a significant positive impact, whereas bank size has a significantly negative effect on profitability.